Programa um computador por aluno: política pública e políticas de subjetivação - Cazonatto, Camilo [UNESP] (2016)
Starting from an inquire on the public policy entitled One Computer per Student Program (PROUCA) [Programa Um Computador por Aluno], the present study sought to assess the biopolitics strategies implemented as government technologies nowadays. Taking the clashing in relationships between the actors on the international setting as its premise, essay's discussion focuses on the possibilities of resistance and capture, trough the assertions made by discourses of truth on digital inclusion and the need to improve the learning process by the use of information and communications technology in the classroom. A critical reading of official documents that gave support to the Federal Government in the adoption of PROUCA, as well as inquiries on the official wiki of the NGO responsible for the dissemination of the methodology adopted in the implementation of this policy, enabled the recognition of the actors involved in it, their roles played through the exercise of power, and the conclusion that these persistent disputes are directly intertwined in the existing social, political and economic regime.